1995
DOI: 10.1159/000284903
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Religious Commitment – A Controlled Study

Abstract: The relationship between psychopathology and religious commitment was explored in a group of psychiatric patients (n = 44) with depression, anxiety disorders and personality disorders, compared with a control group of healthy subjects (n = 45). Neuroticism and the degree of religious involvement were measured in all probands. The findings did not show any correlation between neuroticism and religiosity. While life satisfaction was negatively correlated with neuroticism, there was a significantly positive corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 14 publications
0
25
0
3
Order By: Relevance
“…Moreover, Pokorski & Warzecha stated that -religiosity failed to influence the intensity of depressive symptoms or the strategy of coping with stress in either subgroup, although a trend was noted for better health expectations with increasing religious engagement in depressive subjects‖ [32]. A study from Switzerland investigating the relationship between psychopathology and religious commitment in psychiatric patients and healthy subjects found that there were no correlations between neuroticism and religiosity, while religious commitment was positively associated with life satisfaction [33]. Pfeifer & Waelti concluded that it -is not their personal religious commitment but their underlying psychopathology‖ [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Pokorski & Warzecha stated that -religiosity failed to influence the intensity of depressive symptoms or the strategy of coping with stress in either subgroup, although a trend was noted for better health expectations with increasing religious engagement in depressive subjects‖ [32]. A study from Switzerland investigating the relationship between psychopathology and religious commitment in psychiatric patients and healthy subjects found that there were no correlations between neuroticism and religiosity, while religious commitment was positively associated with life satisfaction [33]. Pfeifer & Waelti concluded that it -is not their personal religious commitment but their underlying psychopathology‖ [33].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Switzerland investigating the relationship between psychopathology and religious commitment in psychiatric patients and healthy subjects found that there were no correlations between neuroticism and religiosity, while religious commitment was positively associated with life satisfaction [33]. Pfeifer & Waelti concluded that it -is not their personal religious commitment but their underlying psychopathology‖ [33].…”
Section: Discussionmentioning
confidence: 99%
“…To measure complex religiosity constructs, we developed a 29-item religiosity scale (Scale available upon request) that borrowed questions from a number of recent scales (Duriez, Soenens, & Hutsebaut, 2005;Koenig, Parkerson, & Meador, 1997;Pfeifer & Waelty, 1995) including items inquiring into areas such as quest (Batson & Schoenrade, 1991), Eastern notions of transcendence and compassion, and the negative phenomenon of stress caused by discordant and conflictual religious beliefs (Exline, Yali, & Sanderson, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Studies with psychiatric inpatients and matched controls have found that the primary factor in patient expression of religious conflicts was their psychopathology, not their level of religious commitment (Pfeifer & Waelty, 1995, 1999. The patients themselves often claim that religion or spirituality played a key role in helping them cope with their symptoms (Fitchett, Burton, & Sivan, 1997;Kroll & Sheehan, 1989;Lindgren & Coursey, 1995).…”
Section: Effects Of Religion and Spiritualitymentioning
confidence: 99%